Improved Particle Swarm Optimization with Deep Learning-Based Municipal Solid Waste Management in Smart Cities - Udayakumar, R.; Elankavi, R.; R. Vimal, V.; Sugumar, R. (RGSA : Revista de Gestão Social e Ambiental, 2023)
Objectives: The Internet of Things (IoT) framework is crucial for improving monitoring applications for smart cities and controlling municipal operations in real time. The most significant issue with applications to smart cities has been the handling of solid waste, which may have negative consequences on the health and well-being of people. Waste management has become a problem that developing and developed nations must face. The management of solid waste is a significant and exciting issue that affects habitats all around the world. Thus, it is necessary to create an efficient method to eliminate these issues or, at the very least, reduce them to a manageable level.